Development of “trainer kit kapasitor” (TRAKTOR) as physics learning media based on science process skills (SPS) - Resty Dwi Asry; Andri Suherman; Asep Saefullah (Universitas Sultan Ageng Tirtayasa, 2020)
This study aimed to discover how the media feasibility and response of a limited trial of Trainer Kit Kapasitor (TRAKTOR)/ Capacitor trainer kit based on Science Process Skills (SPS) as a physics learning media. The method used was research and development (R&D) with the 4-D model. As a physics learning media, TRAKTOR was designed to facilitate some experiment activities, including a experiment in capacitance parallel plate capacitor, circuits of capacitors (series, parallel, series-parallel) charging-emptying capacitor. The results showed that the media is feasible to use, namely, 93.74%, which was categorized as very feasible, and the media obtained students' responses with an excellent category of 85.2%. Based on the result, TRAKTOR can facilitate students' SPS and media suitable for use as a physics learning media.